Pengembangan Buku Siswa Berorientasi Chemo-Entrepreneurship (CEP) Pada Materi Gugus Fungsi Untuk SMA/MA Kelas XII - Selly Dwi Pupasari; Agus Kamaludin (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2020)
This study aimed to develop learning media that is student text book orientated towards Chemo-Entrepreneurship of functional group material. The type of this research was research and development. The development of student text books used the 4-D model which included four stages: define, design, develop, and disseminate. The quality of product was assessed by material experts, media experts, three reviewers and responded by ten students of 12 grade. The instrument used for product quality assessment was Likert scale, while the instrument used to determine the response of students was in the form of a Guttman scale questionnaire. Based on the results of the research of the quality of student textbooks by experts, reviewers, and students, it was obtained a result, in the category of very good.